2021
DOI: 10.3389/fimmu.2021.712781
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide Human β-Defensin-3 Accelerates Wound Healing by Promoting Angiogenesis, Cell Migration, and Proliferation Through the FGFR/JAK2/STAT3 Signaling Pathway

Abstract: In addition to its antimicrobial activity, the skin-derived antimicrobial peptide human β-defensin-3 (hBD-3) promotes keratinocyte proliferation and migration to initiate the wound healing process; however, its effects on fibroblasts, which are the major cell type responsible for wound healing, remain unclear. We investigated the role of hBD-3 in cell migration, proliferation and production of angiogenic growth factors in human fibroblasts and evaluated the in vivo effect of hBD-3 on promoting wound healing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 70 publications
(95 reference statements)
0
60
0
Order By: Relevance
“…The levels of angiogenic factors have been shown to be downregulated in nonhealing chronic wounds [ 44 ]. As a recent study indicated that hBD-3 induced the production of angiogenic factors, such as VEGF, PDGF, and FGF2, by dermal fibroblasts [ 10 ], and because this report demonstrated that hBDs promote ANG secretion by fibroblasts, these findings indicate that hBDs may contribute to angiogenesis, in addition to their antimicrobial and other immunomodulatory activities. Therefore, it is hypothesized that promoting the production or receptor activation of angiogenic factors may be a useful treatment strategy for chronic wounds.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The levels of angiogenic factors have been shown to be downregulated in nonhealing chronic wounds [ 44 ]. As a recent study indicated that hBD-3 induced the production of angiogenic factors, such as VEGF, PDGF, and FGF2, by dermal fibroblasts [ 10 ], and because this report demonstrated that hBDs promote ANG secretion by fibroblasts, these findings indicate that hBDs may contribute to angiogenesis, in addition to their antimicrobial and other immunomodulatory activities. Therefore, it is hypothesized that promoting the production or receptor activation of angiogenic factors may be a useful treatment strategy for chronic wounds.…”
Section: Discussionmentioning
confidence: 62%
“…A recent study indicated that the skin-derived antimicrobial peptide hBD-3 promoted wound healing, angiogenesis, proliferation, and migration in fibroblasts in an in vivo mouse model and in cultured primary human dermal fibroblasts. Furthermore, hBD-3 promoted angiogenesis by enhancing the dermal fibroblast production of angiogenic factors, such as VEGF, PDGF, and FGF [ 10 ]. In this study, we demonstrate that the secretion of another angiogenic factor ANG by fibroblasts was increased not only by hBD-hBD-1, hBD-2, hBD-3, and hBD-4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations